Kegiatan dan peran perempuan pedagang ikan dalam rumah tangga di Pasar Gerbang Raja Mangkurawang Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Vania Meidahani; Elly Purnamasari; Gusti Haqiqiansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
The activity and the role of female fish traders against the Household Income in Gerbang Raja Mangkurawang Market, Tenggarong Sub-district, Kutai Kartanegara Regency. Faculty of Fisheries and Marine Science (supervised by Hj. Elly Purnamasari and Gusti Haqiqiansyah). This study aimed to know the activity of female fish traders in the domestic sector, the public sector (community social activities and productivity), and the average female work time, and to know the contribution of the female fish traders’ income against the household income in Gerbang Raja Mangkurawang Market, Tenggarong Sub-district, Kutai Kartanegara Regency. This study was conducted for 6 months from July to December 2020. The sampling method was purposive sampling by taking 24 respondents as the sample. The analysis method was descriptive analysis and business analysis. The result showed that the activities of female fish traders, including managing the household, taking care of children, and a husband, had an average work time of 4.72 hours of the day or 19.65%. In the public sector, the activity was community social activities, including Moslem forum, Posyandu (integrated health service post), Arisan (regular get-togethers), and PKK (Family Welfare Programme), had an average time of 3.7 hours or 12.80%. Besides, in the public sector, the productive activity, such as selling fish, had an average time of 5.2 hours of the day or 22.05%. The total work time for female fish traders in all activities was 13.8 hours of the day or 54.51%. The average income of female fish traders was IDR 5,185,625 of the month, while the average income of their husbands in the non-fishery sector was IDR 6,087,500 of the month. Further, the contribution of female fish traders’ income was 46.1% against household income. Meanwhile, the contribution of the husband’s income against household income was 53.9%.